2017
DOI: 10.14214/sf.1618
|View full text |Cite
|
Sign up to set email alerts
|

Back to forests in pre-Saharan Morocco? When prickly pear cultivation and traditional agropastoralism reduction promote argan tree regeneration

Abstract: Back to forests in pre-Saharan Morocco? When prickly pear cultivation and traditional agropastoralism reduction promote argan tree regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
(54 reference statements)
0
19
0
3
Order By: Relevance
“…Present since the eighteenth century in the traditional production system as a dietary supplement for men and cattle, the cactus has nowadays taken such vast proportions in terms of surface that it has become a dominant element of the agrarian landscape. From an environmental point of view, the available studies indicate a revival of biodiversity, presenting the prickly pear as a factor of ecological resilience (Genin et al, 2017). Addressed from a socioeconomic angle, besides the income provided to families through this crop, the spreading of prickly pears in this territory seems to have disrupted an agrarian order and a territorial organization set up by generations of farmers and cattle herders.…”
Section: Figure 1: Territory Of Ait Baamrane Within the National Terrmentioning
confidence: 99%
See 2 more Smart Citations
“…Present since the eighteenth century in the traditional production system as a dietary supplement for men and cattle, the cactus has nowadays taken such vast proportions in terms of surface that it has become a dominant element of the agrarian landscape. From an environmental point of view, the available studies indicate a revival of biodiversity, presenting the prickly pear as a factor of ecological resilience (Genin et al, 2017). Addressed from a socioeconomic angle, besides the income provided to families through this crop, the spreading of prickly pears in this territory seems to have disrupted an agrarian order and a territorial organization set up by generations of farmers and cattle herders.…”
Section: Figure 1: Territory Of Ait Baamrane Within the National Terrmentioning
confidence: 99%
“…23 In the territory of Sbouya, there has thus been a shift from two complementary production systems, based on scarce resources managed to ensure their sustainability and relying more or less on outside sources, to a variety of systems whose beneficiaries are little or not present on site, based on an almost unique resource, the prickly pear. The latter appears on the one hand as a local innovation particularly adapted to the context of climate change and rural exodus, contributing to the ecological resilience of the territory (Barthes et al, 2016;Genin et al, 2017). But on the other hand, it is the catalyst for major agrarian transformations of a system hitherto resilient from a socio-territorial point of view and presently threatened by various factors including economic and ecological (in the case of monoculture).…”
Section: Current Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirements for forage palm cultivation, such as climatic conditions, soil texture varying from sandy to clayey, and the variation between nocturnal and diurnal temperatures are all found in Northeast Brazil (Edivani et al, 2013). Genin et al (2017) evaluated the natural regeneration of argania (Argania spinosa) and palm fruit production (Opuntia fícus-indica) in the arid pre-Saharan zone of south-west Morocco. They observed that the perennial planting of palm allied with the exclusion of pasture for cattle, creates conditions favorable for forest recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it requires less water and is more drought tolerant than other tree-based adaptation options, such as growing olive trees. Recently, high economic value attributed to prickly pear fruits and seed oil has been observed as a lucrative benefit that can be achieved while promoting the recovery of native vegetation (Genin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%